Postmortem Findings Associated With SARS-CoV-2: Systematic Review and Meta-analysis. (May 2021) - Satturwar, Swati; Fowkes, Mary; Farver, Carol; Wilson, Allecia M.; Eccher, Albino; Girolami, Ilaria; Pujadas, Elisabet; Bryce, Clare; Salem, Fadi; El Jamal, Siraj M.; Paniz-Mondolfi, Alberto; Petersen, Bruce; et al.
Abstract : Coronavirus Disease 2019 (COVID-19), caused by the novel Severe Acute Respiratory Syndrome–associated Coronavirus 2 (SARS-CoV-2), has become a global threat to public health. COVID-19 is more pathogenic and infectious than the prior 2002 pandemic caused by SARS-CoV-1. The pathogenesis of certain disease manifestations in COVID-19 such as diffuse alveolar damage (DAD) are thought to be similar to SARS-CoV-1. However, the exact pathogenesis of COVID-19 related deaths remains poorly understood. The aim of this article was to systematically summarize the rapidly emerging literature regarding COVID-19 autopsies. A meta-analysis was also conducted based on data accrued from preprint and published articles on COVID-19 (n=241 patients) and the results compared with postmortem findings associated with SARS-CoV-1 deaths (n=91 patients). Both autopsy groups included mostly adults of median age 70 years with COVID-19 and 50 years with SARS-CoV-1. Overall, prevalence of DAD was more common in SARS-CoV-1 (100.0%) than COVID-19 (80.9%) autopsies ( P =0.001). Extrapulmonary findings among both groups were not statistically significant except for hepatic necrosis ( P <0.001), splenic necrosis ( P <0.006) and white pulp depletion ( P <0.001) that were more common with SARS-CoV-1. Remarkable postmortem findings in association with COVID-19 apart from DAD include pulmonary hemorrhage, viral cytopathic effect within pneumocytes, thromboembolism, brain infarction, endotheliitis, acute renal tubular damage, white pulp depletion of the spleen, cardiac myocyte necrosis, megakaryocyte recruitment, and hemophagocytosis. Abstract : Supplemental Digital Content is available in the text.